GLOBAL TRENDS IN MOBILE LEARNING RESEARCH FOR EDUCATION: A BIBLIOMETRIC ANALYSIS - Cik Jamaliah Abd Manaf; Shakinaz Desa; Muhammad Ikhwan Mat Saad (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Mobile Learning (m-Learning) has transformed education by providing accessibility, flexibility, and new learning approaches in a variety of situations. Despite its expanding importance, a thorough grasp of research trends, collaborations, and thematic focus is required to discover advancements and shortcomings in this discipline. This study employs bibliometric analysis to investigate the evolution of "Mobile Learning in Education" using data pulled from the Scopus database. A total of 1,162 publications were analysed using Scopus Analyser and VOSviewer software to map research trends, network collaborations, and topic clusters. The findings show a tremendous rise in m-Learning research over the last two decades, with China and the United States emerging as the primary contributors. Keyword co-occurrence analysis revealed themes such as "mobile learning," "e-learning," "student engagement," and "emerging technologies," which reflect the incorporation of novel methodologies such as augmented reality and gamification into m-Learning. Despite these developments, gaps remain in terms of content quality, inclusivity for marginalised groups, and the long-term impact of m-Learning efforts. The study also identified infrastructure constraints and differences in global adoption rates, particularly in developing countries. The findings emphasise the importance of multidisciplinary frameworks, localised research, and longitudinal studies in improving the scalability and effectiveness of m-Learning. This bibliometric analysis provides useful insights for educators, researchers, and policymakers, offering a thorough overview of the field’s evolution and a strategic direction for future research and application in education systems worldwide.